(untitled) (Journal of Fatima Jinnah Medical University, 2019)
Background: Colorectal cancer (CRC) is a major cause of morbidity and mortality globally and its incidence raising among younger age group in recent years have been observed. The aim of this study was to evaluate the clinical s with colorectal cancer at tertiary care hospital of Karachi. Patients and methods: It was a cross-sectional study conducted at the Oncology Department of Jinnah Postgraduate Medical College, Karachi Pakistan from March 2017 to July 2018. The non-probability consecutive sampling technique was employed. Total of 186 patients aged 16-80 years of either gender with biopsy proven diagnosis of colorectal cancer were included in the study. Patients presented with other large bowel disease or non-malignant tumors confirmed on histopathology were excluded. Information regarding socio-demographic and clinicopathologic factors and treatments were obtained from all the patients. Results: Total of 186 patients were included in the study. Among them, 144 (77.4%) patients were less than 50 years of age and 42 patients (22.6%) were greater or equal to 50 years of age. In all, most of the subjects presented with abdominal pain (17.7%), followed by change in bowel habit (17.2%), weight loss (15.6%), constipation (13.4%), anorexia (11.8%), bleeding per rectum (12.4%), hemotochezia (7.5%) and anemia (4.3%). The rectum was the most frequent site (72.5%) for colorectal cancer, followed by rectosigmoid (8.1%). Microscopically, adenocarcinoma was the most common histopathological tumour in 157 (84.4%) patients followed by mucinous adenocarcinoma (10.8%) and signet ring cell carcinoma (3.8%) and squamous cell carcinoma (2.2%). About 41.9% of the tumors were moderately differentiated. According to the TNM staging of cancer, 42.5% were identified as being in late stages (TNM Stage III & IV) and only 1.6% were in stage 1. Among 186 patients, liver was observed as the most frequent site of metastasis (5.4%). Conclusion: In the present study frequency of colorectal cancer was colorectal cancer found to influence more Pakistani patients at early age as compared to older patients. There is a great need of awareness about the potential factors and screening decisions for CRC in young adults.